Retrospective study of transmissible veneral tumor in dogs (Canis lupus familiaris) in the region of garça, são paulo, brazil - Dos Santos, Ivan Felismino Charas [UNESP]; Ferreira, Gustavo Manea [UNESP]; Silva, Bruna Martins [UNESP]; Branco, Marina Paiva [UNESP]; Ferro, Barbara Sardela [UNESP]; Rahal, Sheila Canevese [UNESP]; Sakata, Stella [UNESP]; Gallina, Marina Frazatti [UNESP] (Medicina Veterinaria (UFRPE), 2021)
The aim of the study was to carry out a retrospective study of transmissible venereal tumor (TVT) in dogs in the region of Garça-São Paulo (SP), from 2012 to 2016, through a study of the existing variables. Data from clinical records and cytopathological and histopathological examinations of veterinary clinics in the region of Garça-SP, from January 2012 to July 2016, were analyzed. The variables included gender, age, breed, body mass, dogs submitted or not to surgical contraception, free access to the street, blood laboratory tests, location and size of TVT, and type and duration of treatment. Twenty dogs with TVT were diagnosed, 80% female and 20% male, with a higher incidence in dogs over the age of six years, cross-bred, with a body mass between nine and 15 kg, not spayed or neutered, and with free access to street. All dogs had leukocytosis and lymphocytosis. In males, TVT was observed only in the foreskin (20%); and in females, the most affected region was the vaginal region (45%). TVTs with sizes between 1 and 3 cm were the most common (50%). The most used treatment protocol was vincristine sulfate every seven days (60%) with an average of 3.7 ± 1.5 applications, followed by the association with doxycycline in positive cases of ehrlichiosis. It was concluded that medium-sized mixed-breed non-castrated adult dogs with free access to the street were those with the highest incidence of TVT and the treatment protocol was with vincristine sulfate.
Estudo retrospectivo de tumor venéreo transmissível em cães (Canis lupus familiaris) na região de garça, são paulo, brasil
Keywords: Canines; Epidemiology; Oncology; Risk factors